Is the duration of pre-operative conservative treatment associated with the clinical outcome following surgical decompression for lumbar spinal stenosis? A study based on the Spine Tango Registry - Zweig, T.; Enke, J.; Mannion, A.; Sobottke, R.; Melloh, Markus; Freeman, B.; Aghayev, E. (Springer, 2016)
Background: The incidence of lumbar spinal stenosis (LSS) continues to rise, with both conservative and surgical management representing options for its treatment. The timing of surgery for LSS varies from shortly after the onset of symptoms to several months or years after conservative treatment. The aim of this study was to investigate the association between the duration of pre-operative conservative treatment and the ultimate outcome following surgical interventions for LSS. Methods: The study was based on prospective multicentre registry data (Spine Tango). Cases of LSS with a documented duration of conservative treatment, undergoing spinal decompression with at least one post-operative patient assessment between 3 and 30 months, were included in the study. Cases of LSS with spondylolisthesis, additional spinal pathology or previous spinal surgery were excluded. Interrogation of the Spine Tango Registry listed 3478 patients meeting the prescribed inclusion criteria. This cohort was stratified into four groups: (1) no previous treatment (n = 497; 14.3%), (2) conservative treatment <6 months (n = 965; 27.8%), (3) conservative treatment between 6 and 12 months (n = 758; 21.8%), and (4) conservative treatment >12 months (n = 1258; 36.1%). Group 4 reference group in regression analysis. The inverse probability of treatment weighting (IPTW) was applied using the propensity score to balance the groups for their characteristics. Outcome measures included achievement of the minimum clinically important change (MCIC) score of 2 points for (a) back pain, (b) leg pain and (c) Core Outcome Measures Index (COMI), and (d) surgical complications, (e) general complications and (f) operation time >2 h. Results: Patient group (“duration of conservative therapy”) was not associated with achievement of the MCIC for post-operative relief of leg pain (p = 0.22), achievement of MCIC for the COMI score (p = 0.054), surgical complications (p = 0.11) or general complications (p = 0.14). Only MCIC for post-operative relief of back pain (p = 0.021) and operation time were significantly associated with patient group (p = 0.038). However, compared with the reference group of >12 months of conservative treatment there was no significant difference in the likelihood of achieving the MCIC for those with none, <6 or 6–12 months of conservative treatment. Conclusions: The duration of pre-operative conservative treatment was not associated with the ultimate outcome of decompression surgery. Further research is required to investigate optimal thresholds/indications for surgery and its appropriate timing in individual patients.